Effects of Repetitive Shoulder Activity on the Subacromial Space in Manual Wheelchair Users. (20th July 2014) - Lin, Yen-Sheng; Boninger, Michael; Worobey, Lynn; Farrokhi, Shawn; Koontz, Alicia
Abstract : This study investigated (1) the effect of repetitive weight-relief raises (WR) and shoulder external rotation (ER) on the acromiohumeral distance (AHD) among manual wheelchair users (MWUs) and (2) the relationship between shoulder pain, subject characteristics, and AHD changes. Twenty-three MWUs underwent ultrasound imaging of the nondominant shoulder in an unloaded baseline position and while holding a WR position before and after the WR/ER tasks. Paired t -tests and Spearman correlational analysis were used to assess differences in the AHD before and after each task and the relationships between pain, subject characteristics, and the AHD measures. A significant reduction in the subacromial space (P < 0.01 ) occurred when subjects performed a WR position compared to baseline. Individuals with increased years of disability had greater AHD percentage narrowing after WR (P = 0.008 ). Increased shoulder pain was associated with AHD percentage narrowing after ER (P ≤ 0.007 ). The results support clinical practice guidelines that recommend MWUs limit WR to preserve shoulder function. The isolated repetitive shoulder activity did not contribute to the changes of subacromial space in MWUs. The ultrasonographic measurement of the AHD may be a target for identifying future interventions that prevent pain.